PENGARUH OBEDIENCE PRESSURE DAN SELF-EFFICACY TERHADAP AUDIT JUDGEMENT PADA AUDITOR PERWAKILAN BPKP PROVINSI SULAWESI UTARA - Rumengan, Vriska; Tinangon, Jantje J.; Pangerapan, Sonny (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
BPKP is one of the official internal government auditors, whose duties and functions is to supervised financial and development activities. One of its task is to audit. When conduction an audit, auditors are required to be able to give consideration as to the supervision of the government financial statements. This is where the role of audit judgement comes to life. Audit judgement is the personal consideration of auditors in decision making whether or not a financial statement is reasonable. Audit judgement is effected by several factors, that is Obedience Pressure and Self-efficiency. This research is aimed to find out the impacts of obedience pressure and self efficiency on audit judgement. The sample of this research is 53 auditors employed at the Offices of The Representatives of BPKP, North Sulawesi, in Manado. The samples were chosen randomly using simple random sampling techniques. The data were analyzed using multiple regression analysis and the data were examined using SPSS 21 (Statistical Product and Service Solution). The result of this research showed that partially, obedience pressure significantly influence the audit judgement negatively; while self-efficiency significantly influence audit judgement positively. Keywords: Audit Judgement, Obedience Pressure, Self-Efficacy.